2022
DOI: 10.1111/jfb.15068
|View full text |Cite
|
Sign up to set email alerts
|

Length–weight relationships of 55 mesopelagic fishes from the eastern tropical North Atlantic: Across‐ and within‐species variation (body shape, growth stanza, condition factor)

Abstract: We present estimates of length-weight relationships (LWRs) of 55 mesopelagic fish species of 13 taxonomic families based on data collected in the eastern tropical North Atlantic (ETNA) in March/April 2015. Our data include novel records for 19 species, while for 25 species LWRs are based on the most robust sample sizes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Although differences were not significant, net catches showed a tendency for higher biomass, and a higher relative contribution of larger sizes in the more productive Lisboa zone. Taking into account the positive allometric growth of mesopelagic fish (Eduardo et al, 2019;Loṕez-Peŕez et al, 2020;Czudaj et al, 2022) and that our trawl system is biased towards small fish, our results suggest that the differences would be even higher if larger size classes had been collected, and therefore the most productive zone would have a higher overall biomass.…”
Section: Vertical Patternsmentioning
confidence: 59%
“…Although differences were not significant, net catches showed a tendency for higher biomass, and a higher relative contribution of larger sizes in the more productive Lisboa zone. Taking into account the positive allometric growth of mesopelagic fish (Eduardo et al, 2019;Loṕez-Peŕez et al, 2020;Czudaj et al, 2022) and that our trawl system is biased towards small fish, our results suggest that the differences would be even higher if larger size classes had been collected, and therefore the most productive zone would have a higher overall biomass.…”
Section: Vertical Patternsmentioning
confidence: 59%
“…With regard to the timing of sampling, this cruise covered the months March and April, and reproductive processes during other seasons have not been investigated. Still, although there appear to be some sampling gaps particularly for larger M. polylepis, the individuals from this cruise range from small and immature to actively spawning and reach or exceed the maximum lengths so far reported (Czudaj et al, 2022;Hulley, 1990) in each species. The three species were selected for analysis because a sufficiently large number of individuals had been caught, and damaged specimens with gonads visible indicated that a range of ovarian developmental phases were present.…”
Section: Methodological Constraintsmentioning
confidence: 62%
“…E. risso undertakes vertical migrations of a limited amplitude (Czudaj et al, 2021). It reaches a maximum length of 84 mm (Czudaj et al, 2022), and its diet consists of planktonic copepods as well as small mesopelagic fish (Battaglia et al, 2016). The family Melamphaidae is an abundant but understudied family of meso-to bathypelagic fishes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Diaphus-slender morphotype has a more streamlined shape that improves their prolonged swimming ability [ 62 ]. In addition, according to the body shape [ 63 ] two additional morphotypes were described for Diaphus spp. (fusiform: D. dumerilii , D. vanhoeffeni, and L. dofleini ; elongatum: D. fragilis ).…”
Section: Discussionmentioning
confidence: 99%